2012
DOI: 10.1089/gtmb.2011.0099
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of theCYP21A2Gene in the Iranian Population

Abstract: Background: Defects in the CYP21A2 gene cause steroid 21-hydroxylase deficiency, which is the most frequent cause of congenital adrenal hyperplasia. Forty four affected families were investigated to identify the mutation spectrum of the CYP21A2 gene. Methods: Families were subjected to clinical, biochemical, and molecular analyses. Allele-specific polymerase chain reaction amplification was used for eight common mutations followed by dosage analysis to exclude CYP21A2 deletions. Results: The most frequent muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 46 publications
1
24
1
Order By: Relevance
“…A few molecular studies have been published about CAH patients in Iran, and all of them have worked on CYP21A2 gene mutations (Vakili et al, 2005;Ramazani et al, 2008;Rabbani et al, 2011a). In this study, a homozygous coding mutation is reported in a 20 day old pseudohermaphrodite male due to substitution of G to C of codon 82 (at position 244), encompassing the membrane binding domain of 3βHSD enzyme.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A few molecular studies have been published about CAH patients in Iran, and all of them have worked on CYP21A2 gene mutations (Vakili et al, 2005;Ramazani et al, 2008;Rabbani et al, 2011a). In this study, a homozygous coding mutation is reported in a 20 day old pseudohermaphrodite male due to substitution of G to C of codon 82 (at position 244), encompassing the membrane binding domain of 3βHSD enzyme.…”
Section: Discussionmentioning
confidence: 71%
“…Males would present hypospadias, and ambiguous genitalia; females would show normal or mild virilized external genitalia because this deficiency lowers the testosterone concentration for development of external genitalia (Pang, 1998). Molecular analysis of Iranian CAH patients has been carried out for CYP21A2 gene (Vakili et al, 2005;Ramazani et al, 2008;Rabbani et al, 2011aRabbani et al, , 2011b which accounts for more than 95% of the CAH defects in Iran. However, the remaining causal defects of CAH are unknown among this population.…”
Section: Introductionmentioning
confidence: 99%
“…First, we analyzed a heterogeneous population as opposed to past reports, which were drawn from specific countries (18)(19)(20). Second, our data provide a framework for physicians to ascertain the prevalent form of CAH for a given genotype.…”
mentioning
confidence: 99%
“… 4 Recent studies showed that an IVS2 AS -13 (A/C to G) mutation is prevalent in the Iranians while p.Q319X is common in Turkey, Tunisia, and East India. 4 - 7 Different mutations result in variable deficiency of cortisol and aldosterone together with increased synthesis of androgen. 8 - 10 The genotype/phenotype correlation of CAH has been reported in different populations and ethnic groups.…”
mentioning
confidence: 99%
“… 8 - 10 The genotype/phenotype correlation of CAH has been reported in different populations and ethnic groups. 4 - 7 Although the clinical presentations of CAH have been studied in Saudi children, literature review revealed no molecular report of 21-hydroxylase. 3 Therefore, the aim of this study was to determine the pattern of CYP21A2 gene-mutations in Saudi children with CAH, and to describe the clinical phenotype of these patients.…”
mentioning
confidence: 99%